Real-Time Evaluation of Rain-Induced Signal Degradation on Digital Satellite Television Links in Minna, Nigeria - Kingsley C. IGWE; Abubakar T. MUHAMMAD; Obiseye OBIYEMI; Abiodun S. MOSES; Aku G. IBRAHIM; Joel A. EZENWORA; Julia O. EICHIE (FUDMA Journal of Engineering and Technology, 2025)
This paper documents the results of the investigation of real-time evaluation of rain-induced signal degradation on digital satellite television links in Minna (9o 37''N, 6o 30''E), Nigeria. Two aspects of analyses are involved. One is the prediction of rain-induced attenuation for earth-space links at Ku band using the ITU-R P.618-12 attenuation model, while the other is the real-time measurement of the exact television signal strength during clear sky and during rainfall. This study was set up as a preliminary assessment. The results obtained revealed significant differences between the predicted and the measured rain attenuation values. The ITU-R P.618-12 model predicted an attenuation value of 16 dB at 0.01%-time exceedance. For the real-time signal measurement, signal levels that ranged between 80 and 83 dBµV were recorded during clear sky. However, during rainfall, these values degraded to the range of 69 to 78 dBµV, thereby resulting to a range of 5 - 11 dBµV signal level degradation.
Keywords: Digital satellite television, rain rate, rain attenuation, real-time evaluation.